Organic dye molecules as reducing agent for the synthesis of electroactive gold nanoplates - Sharma, Jadab; Vijayamohanan, Kunjukrishna P. (Journal of Colloid and Interface Science, 2006)
Highly crystalline, hexagonal and triangular nanoplates of gold are synthesized in high yield by a new wet chemical method using multifunctional molecules. Bismarck brown R (BBR) and Bismarck brown Y (BBY). This method involves a simple approach by keeping a mixture of aqueous HAuCl(4) solution and BBR/BBY solution in presence of poly(vinyl pyrrolidone) for 24 h. These nanostructures show unprecedented electrochemical properties exhibiting Surface confinement effect. The UV-visible (UV-vis) spectrum shows certain distinct features with absorptions at 300, 400,and 650 nm extending up to the near infrared region. Selected area electron diffraction patterns of these nanoparticles show highly oriented (111) crystal facets. X-ray diffraction analysis also confirms the Predominant orientation in the (111) crystal planes with lattice constant similar to 4.07 angstrom of face-centered-cubic (fcc) gold. X-ray photoelectron (XP) and Fourier transform infrared (FTIR) spectroscopic analysis shows the presence of a fraction of reducing molecules as surface passivating agent either in the unreacted molecular state or as a mixture of reacted and unreacted product which probably undergoes charge transfer with gold nanocrystals giving absorption at similar to 300 nm. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Bismarck brown; cyclic voltammetry; gold nanoplates; poly(vinyl pyrrolidone); surface plasmon resonance

Plasmon-enhanced photocurrent generation from click-chemically modified graphene - Yenchalwar, Sandeep G.; Devarapalli, Rami Reddy; Deshmukh, Ashvini B.; Shelke, Manjusha V. (Chemistry-A European Journal, 2014)
The visible-light response of Au nanoparticles (AuNPs) assembled on rGO through different molecular bridges was investigated by transient photocurrent generation. We prepared rGO with two self-assembled monolayers (SAMs), one linear and the other with aromatic triazoles through a click cycloaddition reaction. A fivefold photocurrent enhancement was observed for triazole linkers over the aminopropyltrimethoxysilane (APTMS) linker. Cyclic voltammetry (CV) and impedance measurements also suggest fast electron transfer on account of the low resistance offered by the click-modified rGO surface whereby introduction of triazoles offers the efficient bridge between the donor AuNPs and acceptor rGO.
Keywords: Gold; graphene; Nanoparticles; photophysics; surface plasmon resonance

Electronic integration and thin film aspects of Au-Pd/rGO/TiO2 for improved solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala P.; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2019)
In the present work, we have synthesized noble bimetallic nanoparticles (Au-Pd NPs) on a carbon-based support and integrated with titania to obtain Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2 nanocomposites using an ecofriendly hydrothermal method. Here, a 1:1 (w/w) Au-Pd bimetallic composition was dispersed on (a) high-surface-area (3000 m(2) g(-1)) activated carbon (Au-Pd/C), prepared from a locally available plant source (in Assam, India), and (b) reduced graphene oxide (rGO) (Au-Pd/rGO); subsequently, they were integrated with TiO2. The shift observed in Raman spectroscopy demonstrates the electronic integration of the bimetal with titania. The photocatalytic activity of the above materials for the hydrogen evolution reaction was studied under 1 sun conditions using methanol as a sacrificial agent in a powder form. The photocatalysts were also employed to prepare a thin film by the drop-casting method. Au-Pd/rGO/TiO2 exhibits 43 times higher hydrogen (H-2) yield in the thin film form (21.50 mmol h(-1) g(-1)) compared to the powder form (0.50 mmol h(-1) g(-1)). On the other hand, Au-Pd/C/TiO2 shows 13 times higher hydrogen (H-2) yield in the thin film form (6.42 mmol h(-1) g(-1)) compared to the powder form (0.48 mmol h(-1) g(-1)). While powder forms of both catalysts show comparable activity, the Au-Pd/rGO/TiO2 thin film shows 3.4 times higher activity than that of Au-Pd/C/TiO2. This can be ascribed to (a) an effective separation of photogenerated electron-hole pairs at the interface of Au-Pd/rGO/TiO2 and (b) the better field effect due to plasmon resonance of the bimetal in the thin film form. The catalytic influence of the carbon-based support is highly pronounced due to synergistic binding interaction of bimetallic nanoparticles. Further, a large amount of hydrogen evolution in the film form with both catalysts (Au-Pd/C/TiO2 and Au-Pd/rGO/TiO2) reiterates that charge utilization should be better compared to that in powder catalysts.
Keywords: bimetal; Photocatalysis; surface plasmon resonance; TiO2; water splitting

Bioinspired synthesis of multifunctional silver nanoparticles for enhanced antimicrobial and catalytic applications with tailored SPR properties - Parit, S. B.; Karade, V. C.; Patil, R. B.; Pawar, V. N.; Dhavale, R. P.; Tawre, M.; Pardesi, K.; Jadhav, U. U.; Dawkar, V. V.; Tanpure, R. S.; Kim, J. H.; Jadhav, J. P.; et al. (Materials Today Chemistry, 2020)
In the developing nanotechnology world, numerous attempts have been made to prepare the nobel metallic nanoparticles (NPs), which can improve their applicability in diverse fields. In the present work, the biosynthesis of silver (Ag) NPs has been successfully achieved through the medicinal plant extract (PE) of G. resinifera and effectively used for the catalytic and antibacterial applications. The size dependant tuneable surface plasmon resonance (SPR) properties attained through altering precursor concentrations. The X-ray and selected area diffraction pattern for Ag NPs revealed the high crystalline nature of pure Ag NPs with dominant (111) phase. The high-resolution TEM images show the nonspherical shape of NPs shifting from spherical, hexagonal to triangular, with wide particle size distribution ranging from 13 to 44 nm. Accordingly, the dual-band SPR spectrum is situated in the UV-Vis spectra validating the non-spherical shape of Ag NPs. The functional group present on the Ag NPs surface was analysed by FT-IR confirms the capping and reducing ability of methanolic PE G. resinifera. Further, the mechanism of antimicrobial activity studied using electron microscope showed the morphological changes with destructed cell walls of E. coli NCIM 2931 and S. aureus NCIM 5021 cells, when they treated with Ag NPs. The Ag NPs were more effective against S. aureus and E. coli with MIC 128 mu g/ml as compared to P. aeruginosa NCIM 5029 with MIC 256 mu g/ml. Apart from this, the reduction of toxic organic pollutant 4-NP to 4-AP within 20 min reveals the excellent catalytic activity of Ag NPs with rate constant k = 15.69 s(-1). (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Ag NPs; Antibacterial; Catalytic activity; Gardenia resinifera; surface plasmon resonance

Ultra-small Au nanoclusters with tailored photoluminescence properties using modified thiol ligands: a computational and experimental demonstration - Chahande, Anurag M.; Maibam, Ashakiran; Krishnamurty, Sailaja; Devi, R. Nandini (Particle & Particle Systems Characterization, 2024)
Au nanoclusters with tailored photoluminescence can be obtained through controlled nanoparticle ligand interface chemistry. The present work reports molecular gold nanoclusters with tuneable photoluminescence emission from 600 to 700 nm using N,N `,N `'-trialkyl (11-mercaptoundecyl)ammonium chloride ligands as capping-agents. The tunability within red spectral region is regulated through specific interface chemistry between gold nanoclusters of molecular range and functional groups of the quaternary ammonium head over N,N `,N `'-trialkyl(11-mercaptoundecyl)ammonium chloride. Combined understanding obtained from the spectroscopy, microscopy, and density functional theory studies demonstrate that the functional group specific electronic interactions at the interfaces steer the emission characteristics of ``molecular'' Au nanoparticles. The study clearly identifies that bulkier functional groups, i.e., triethyl, tripropyl, tributyl, and dimethyl benzene over N+ (of thiol ligand) through their steric effects minimize the particle size giving rise to tunable photoluminescence emission in red spectral region. However, the red shift seen in the emission Au nanoclusters with N-(11-mercaptoundecyl)-N,N `-dimethylbenzenammonium chloride ligand in contradiction to particle size effect is computationally proved to be due to the delocalization of electron density from benzene aromatic ring to N+ of ammonium head leading to a reduction in the HOMO-LUMO energy gap. Fluorescence properties of water dispersible Au nanoclusters are tuned by varying the ammonium head group. Density Functional Theory studies correlate the distinction in emission when head group is phenyl to charge transfer characteristics. image
Keywords: Density functional theory; photoluminescent Au nanoclusters; surface plasmon resonance; thiol ligand